Employers and the gender wage gap - John Forth; Nikolaos Theodoropoulos (IZA World of Labor, 2023)
In most developed countries, women have closed the gap in educational attainment and labor market experience, yet gender wage gaps persist. This has led to an increased focus on the role of employers and employment practices. In particular, research has focused on the types of workplace where men and women work, their promotion prospects and the extent to which they are rewarded differently for similar work. Understanding the relative importance of these features, and the mechanisms that generate them, is necessary to design effective policy responses.
Keywords: H55; J16; J31; I18; M52; M54; 330; sorting; bargaining; discrimination; promotion; motherhood; flexibility